Analisis Yuridis Putusan MK Nomor 313/PHPU-BUP.XXIII/2025 dalam Penyelesaian Sengketa Hasil Pemilihan Bupati - Rahmat Sabrianto; Ahmad Rustan; Rudy Iskandar Ichlas (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Disputes over the results of the Regional Head Election (Pilkada) are a consequence of the dynamics of democracy in Indonesia, which demands a fair and constitutional resolution mechanism. One prominent case is the Constitutional Court Decision Number 313/PHPU-BUP.XXIII/2025 concerning the 2024 Regent and Deputy Regent Election of North Barito Regency, which involved alleged vote buying practices in the revote (PSU). This study aims to analyze the Constitutional Court's legal considerations in deciding the case, particularly regarding violations of vote buying, consistency with democratic principles, and its implications for legal certainty. The method used is normative legal research with an approach of legislation, doctrine, and analysis of court decisions. The results show that the Constitutional Court prioritizes a substantive approach by assessing not only the vote count results but also the integrity of the election process. The practice of money politics that is proven to be structured, systematic, and massive (TSM) is considered to undermine democratic principles, so the Constitutional Court imposed sanctions on the candidate pairs and ordered a revote. This ruling affirms the Constitutional Court's role as the guardian of the constitution and democracy and strengthens legal certainty, although it still raises debate regarding the proportionality of sanctions and the protection of political rights.